Kawasaki disease. Presentation of two cases - Kenly Armas-Esquijarosa (Centro Editorial Ciencias Médicas: CPICM Guantánamo, 2021)
Kawasaki disease is a rare medical condition. Young children are the most affected and the cardiovascular complications of the disease are feared the most. Two cases diagnosed in the pediatric service of the Hospital General Docente de Placetas, Villa Clara, were described in this article. Both patients, preschoolers, presented common symptoms, such as: fever for more than 5 days, lymphadenopathy, non-suppurative conjunctivitis, edema of the back of the hands and feet, a strawberry tongue and rash. The clinical elements were, once again, the cornerstone for the diagnosis. Both patients evolved favorably to the treatment used and did not develop serious forms or sequelae of the disease.